IMPLEMENTASI PERATURAN DAERAH KABUPATEN PONOROGO NOMOR 1 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH (RTRW) DALAM PEMANFAATAN RUANG TERBUKA HIJAU (RTH) - Gilang Gunawan Putra (Master of Public Administration, Universitas Slamet Riyadi, 2023)
This study aims to describe the implementation of regional spatial planningpolicies in the use of green open spaces in Ponorogo Regency, and describe whatfactors influence the implementation of regional spatial planning policies in theuse of green open spaces in Ponorogo Regency.The type and analysis of data used a descriptive qualitative approach. Sources ofdata consist of primary data in the form of direct interviews and secondary data isdata collected from observations and institutional literature related to research.Data collection techniques using interviews, observation and documentation.Data analysis techniques with data reduction, data presentation and drawingconclusions. Test the validity of the data using data source triangulationtechniques and member check.This study uses the Edward III Implementation theory, the results of the studyshow that the implementation of Spatial Planning Policy in the utilization ofGreen Open Space in Ponorogo Regency is generally carried out well, things thathave been implemented are realization, socialization, and reports from SKPDrelated to the implementation of the Ponorogo Regency Regional RegulationNumber 1 of 2012 concerning Regional Spatial Planning in Utilization of GreenOpen Space. Implementation of the Spatial Planning Policy in the use of GreenOpen Space in Ponorogo Regency from the communication aspect, in principlethe Regency Government has socialized the city's spatial plan. Aspects ofresources are sufficient, but still lacking in quantity and quality. Aspect ofdisposition, policy implementers have quite good characteristics.Keywords: Implementation, Regulations, Green Open Space